1989
DOI: 10.1007/bf01972796
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SK&F 86002 on cytokine production by human monocytes

Abstract: Human monocytes respond to a variety of stimuli in vitro by producing a number of physiologically important macromolecules including the cytokines. SK&F 86002, a dual inhibitor of the arachidonate metabolism, has been shown to inhibit LPS induced IL-1 production in human monocytes. We examined its effect on the production of other cytokines which are coordinately expressed as a result of LPS stimulation such as tumor necrosis factor alpha (TNF), alpha interferon (IFN-A), interferon beta-2 (IL-6) and granulocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…However, in dysregulated settings, the same products mediate inflammation and tissue damage. Several years ago, a class of pyridinyl imidazoles were observed to suppress the production of two inflammatory cytokines, tumor necrosis factor ␣ (TNF-␣) and interleukin-1␤ (IL-1␤) [1][2][3]. Later, in an elegant study, Lee et al [4] determined that the molecular target of these compounds was a kinase, now generally referred to as p38 mitogen-activated protein kinase (p38).…”
Section: Introductionmentioning
confidence: 99%
“…However, in dysregulated settings, the same products mediate inflammation and tissue damage. Several years ago, a class of pyridinyl imidazoles were observed to suppress the production of two inflammatory cytokines, tumor necrosis factor ␣ (TNF-␣) and interleukin-1␤ (IL-1␤) [1][2][3]. Later, in an elegant study, Lee et al [4] determined that the molecular target of these compounds was a kinase, now generally referred to as p38 mitogen-activated protein kinase (p38).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that SK&F 86002 inhibits IL-1 and TNF-~ production from human monocytes [4]. Table 1 shows that the pyridinyl imidazole compounds, represented by SK&F 86002 and two analogs, also inhibited TNF-~ production from the RAW 264.7 cell line and oil elicited murine peritoneal macrophages.…”
Section: Resultsmentioning
confidence: 90%
“…Given the increasing evidence that TNF-~ plays an important role in many pathophysiological processes, the modulation of this cytokine may have a beneficial effect in inflammatory disease states. SK&F 86002, a pyridinyl imidazole anti-inflammatory compound [3] has previously demonstrated inhibitory effects on human monocyte IL-1 and TNF-~ production [4]. In this study we report that SK&F 86002 and its analogs also inhibit TNF-e production from two murine cell types in a * Author for correspondence.…”
Section: Introductionmentioning
confidence: 77%
“…NF-kB or p38 MAPK) without the adverse and off-target effects of NSAIDs. 23,24 Examples include: TPCA1 (5-[p-fluorophenyl)-2-ureido] thiophene-3-carboxamide), an inhibitor of the IkB kinase subunit beta (IKK-b) that has been shown to reduce LPS-stimulated choriodecidual inflammatory gene expression with no effects on apoptosis; 25 NF-kB essential modulator (NEMO) binding domain inhibitor (iNBD), a cell-permeable peptide that inhibits activation of the IKK complex via NBD blockade that has been shown to inhibit a wide range of inflammatory responses in animal models; [26][27][28]…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB or p38 MAPK) without the adverse and off-target effects of NSAIDs. 23,24 Examples include: TPCA1 (5-[ p -fluorophenyl)-2-ureido] thiophene-3-carboxamide), an inhibitor of the IκB kinase subunit beta (IKK-β) that has been shown to reduce LPS-stimulated choriodecidual inflammatory gene expression with no effects on apoptosis; 25 NF-κB essential modulator (NEMO) binding domain inhibitor (iNBD), a cell-permeable peptide that inhibits activation of the IKK complex via NBD blockade that has been shown to inhibit a wide range of inflammatory responses in animal models; 2628 SB239063 (trans-1-[4-hydroxycyclohexyl]-4-[4-fluorophenyl]-5-[2-[methoxy]pyrimidin-4-yl]imidazole), a MAPK inhibitor successfully used to block inflammation in animal models and in human fetal membranes; 29,30 and 5 z-7-oxozeaenol (OxZ), a selective inhibitor of TGF-β activated kinase 1 (TAK1, also known as MAP3K7) that has been shown to inhibit pro-inflammatory mediator production in murine fibroblasts, 31 primary cortical neurons, 32 dermal fibroblasts 33 and ear swelling models. 31 We recently compared the effects of NAC and three of these CSAIDs (SB239063, TPCA1 and iNBD) on human and ovine gestational membranes stimulated ex vivo with γ-irradiation-killed Escherichia coli and showed that TPCA1 and SB239063, and to a lesser extent NAC, effectively suppressed cytokine and prostaglandin production within just 3 h. 20 Furthermore, we have shown in a large animal model of LPS-induced chorioamnionitis that intra-amniotic administration of a single dose of TPCA1 or OxZ can suppress LPS-induced intra-amniotic inflammatory responses, while fetal effects were minimal.…”
Section: Introductionmentioning
confidence: 99%